The Causes And Effects Of Women's Superiority Towards Men As Seen In Aristhophanes’ Lysistrata - Riri Narasati Narasati (Universitas Muria Kudus, 2019)
The differences between man and women as superior and inferior appears in every aspect of life, this differences appears in literary works too. One of the literary works uses superior and inferior themes is Lysistrata that descibes Greece society. The purpose of the research shows women can be a superior in Lysistrata. The reseach uses descriptive qualitative method for processing data from Lysistrata. The research uses Feminism theory focus on marriage contract and women superiority. The result of this reseach shows women can be superior than men by special treatment and women sacrifice. Keywords: feminism, women, women’s superiority.